BENEFITS OF BREASTFEEDINIG FOR MOTHER AND CHILD - Miolski, Jelena (Sanamed, 2023)
Breastfeeding is the best way to feed a child from the first six months until the end of the second year. The unbreakable bond during pregnancy between a mother and her child continues during the lactation process, providing numerous benefits for both the mother and the child. Due to the effects of many hormones after childbirth, lactation offers numerous advantages for the mother. Oxytocin causes reduction of the uterus and bleeding, absence of menstruation, faster return of body weight, lower risk of cancer of the reproductive organs, and prevents the occurrence of osteoporosis and the development of the metabolic syndrome. Breastfeeding certainly ensures a better emotional bond with the child. Specificity in the composition of human milk provides the newborn with short-term and long-term protective effects. Thanks to human oligosaccharides, immunoglobulins, and polyunsaturated fatty acids that influence the composition of the microbiome of the newborn’s intestine, as well as the formation of its immune response, breastfed children suffer less from respiratory and digestive infections, food allergies, autoimmune diseases and have been proven to have a higher IQ. Breastfeeding is the best form of feeding for mother and child. The specificity of the composition of human milk ensures optimal growth and development of the child and a healthier life for its mother.